By-catch Reduction in the World's Fisheries - Kennelly, Steven J. (Reviews: Methods and Technologies in Fish Biology and Fisheries, 2007)
This book comes after several decades of outstanding and successful research that has helped ameliorate some of the most important and controversial fisheries issues in the world - those associated with the unwanted wastage of fish from by-catch and discarding. The 8 chapters encompass contributions from 27 of the world's leading experts in by-catch reduction. They take the reader through most aspects of the field at a variety of scales and viewpoints. They examine the methodologies used to develop by-catch reduction techniques and provide new avenues for assisting and broadening such work. Case studies are provided that encompass most of the world's fishing techniques and regions. Solutions developed for the most problematic fishing methods in terms of by-catch, selectivity and habitat damage are examined in significant detail in addition to ways to reduce the by-catch of charismatic species like marine mammals and sea-birds. By-catch reduction in less infamous fishing methods is also examined with chapters on recreational fishing and trapping. The book shows how the lessons learned in reducing by-catch can be applied to ameliorate emerging, broader issues concerning the impacts of fishing on entire ecosystems. Finally, the book examines the most vital phase of by-catch reduction work - its uptake and extension into fishing practices. This book will prove an invaluable tool for any fisheries professional or lay person interested in by-catch reduction or, indeed, anyone trying to resolve a particular by-catch problem in their fishery.